Rare Earth Element Speciation in Miocene Brown Coals from the Sergeevskoe Deposit (Priamurie, Far East); Solid Fuel Chemistry; Vol. 56, iss. S1 - Radomskaya V. I. Valentina Ivanovna; Shumilova L. P. Lyudmila Pavlovna; Noskova L. P. Lidiya Petrovna; Sorokin A. P. Anatoly Petrovich; Pavlova L. M. Lyudmila Mikhaylovna; Dugin S. V. Sergey Vadimovich; Soktoev B. R. Bulat Rinchinovich; Poselyuzhnaya A. V. Anna Vladimirovna; Ivanov V. V. Vladimir Viktorovich (2022, 2022)
Title screen